Severe psychiatric disorders in mid-life and risk of dementia in late-life (age 65-84 years): A population based case-control study - Zilkens, Renate; Bruce, D.; Duke, Janine; Spilsbury, Katrina; Semmens, James (Bentham Science, 2014)
Objective: To examine the association of mid-life exposure to several psychiatric disorders with the development of late-life dementia. Methods: A matched case-control study using Western Australian state-wide hospital inpatient, outpatient mental health and emergency records linked to death records. Incident dementia cases (2000-2009) aged 65 to 84 years were sex- and age-matched to an electoral roll control. Records as far back as 1970 were used to assess exposure to medical risk factors before age 65 years. Candidate psychiatric risk factors were required to be present at least 10 years before dementia onset to ensure direction of potential causality. Odds ratios were estimated using conditional logistic regression. Results: 13, 568 dementia cases (median age 78.7 years, 43.4 % male) were matched to a control. Depression, bipolar disorder, schizophrenia, anxiety disorder and alcohol dependence were found to be significant and independent risk factors for late-life dementia after adjusting for diabetes, heart disease, cerebrovascular disease and smoking risk factors. The effect of a history of depression, schizophrenia and alcohol dependency on dementia risk varied with age, being strongest for earlier onset late-life dementia and waning at older ages. Conclusion: Severe depression, anxiety disorder, bipolar disorder, schizophrenia and alcoholic dependency disorder treated by specialists in psychiatric facilities in mid-life are important risk factors for late-life dementia. These psychiatric conditions need to be considered in future studies of the risk and prevention of late-life dementia.